Modelling two layer Mn–Fe–Si–P materials in an active magnetic regenerator. (October 2019) - Christiaanse, T.V.; Trevizoli, P.V.; Rowe, A.
Abstract: A comparison study is performed between results obtained from experiments and modelling of single and multi-layer Mn–Fe–Si–P regenerators. This work builds on top of previously published work describing Mn–Fe–Si–P material data, a numerical system model validated with Gd spheres and experiments using Mn–Fe–Si–P regenerators. To take into account the hysteresis of the material a framework is proposed for the numerical model. The inclusion of hysteresis improves the simulation outcomes when compared to experimental results of a single layer. After correcting single layer results for hysteresis, multi-layered regenerators simulation results are compared to experimental results. Two methods to account for pressure drop are tested and the difference in modelling results are discussed.